Protein structure-sensitive electrocatalysis at dithiothreitol-modified electrodes - Ostatná, Veronika; Cernocká, Hana; Palecek, Emil (Journal of the American Chemical Society, 2010)
Dithiothreitol (DTT)-mercury and DTT-solid amalgam electrodes are proposed for protein microanalysis by means of constant current chronopotentiometric stripping (CPS). At the DTT-modified hanging mercury drop electrode (DTT-HMDE), proteins at nanomolar concentrations produce the CPS peak H, which is due to the protein catalyzed hydrogen evolution. Self-assembled monolayers (SAMs) of DTT at the electrode surface protected surface-attached proteins from the electric field-driven denaturation, but did not interfere with the electrocatalysis. Using CPS peak H, native and denatured forms of bovine serum albumin (BSA) and of other proteins were easily distinguished. On the other hand, in usual slow scan voltammetry (scan rates between 50 mV/s and 1 V/s), the adsorbed BSA behaved as fully or partially denatured. BSA-modified DTT-HMDE was exposed to different potentials, E(B) for 60 s, followed by CPS measurement. Three E(B) regions were observed, in which either BSA remained native (A, -0.1 to -0.3 V), was denatured (B, -0.35 to -1.4 V), or underwent desorption (C, at potentials more negative than -1.4 V). At potentials more positive than the reduction potential of the DTT Hg-S bond (approximately -0.65 V against Ag|AgCl|3 M KCl), the densely packed DTT SAM was impermeable to [Ru(NH(3))(6)](3+). At more negative potentials, the DTT SAM was disturbed, but under conditions of CPS (with very fast potential changes), this SAM still protected the protein from surface-induced denaturation. Thiol-modified Hg electrodes in combination with CPS represent a new tool for protein analysis in biomedicine and proteomics.
Keywords: sérový albumin hovězí; katalýza; dithiothreitol; Protein Denaturation; proteiny; Serum Albumin, Bovine; Hydrogen; Catalysis; denaturace proteinů; vodík; Protein Conformation; elektrochemické techniky; zvířata; Electrochemical Techniques; Dithiothreitol; elektrody; Proteins; Electrodes; konformace proteinů; Animals